(untitled) (Research, Society and Development, 2022)
The skin and intestine are directly interconnected, when the microbiota is in imbalance, the body becomes susceptible to aesthetic dysfunctions, such as acne. In this context this study aims to address the use of probiotics in the treatment of acne through the development of a dermocosmetic with nanotechnological active ingredient containing probiotic SynBiotics Bifidum® (Bifidobacterium Lisado). The research is of experimental and qualitative nature, in which the manipulation of a dermocosmetic was performed. To evaluate the quality control of this study it was analyzed the stability of the formulation, which provides indications about the behavior of the product, where the dermocosmetic was placed in quarantine for 7 and 30 days, facing environmental conditions. For the stability of this product the organoleptic, physicochemical and microbiological characteristics were considered, in order to guarantee a reliable, safe and effective formulation for patients. Five healthy university students with acnes grade I and II were selected, 4 female and 1 male, aged between 20 and 28 years, in which a questionnaire was applied and an individualized consultation was made with each participant. In the analysis of the studies, it was possible to observe that the use of probiotics in the participants showed beneficial effects on skin health, such as the improvement of acne, hydration and slight whitening. The use of probiotics for the promotion of well-being, prevention and treatment of diseases has shown to be relevant, but the number of studies on this theme is still limited when compared to other probiotics Bifidobacterium Lisado for the treatment of acneic skin.